Iron status of 9- and 15-y-old Icelanders. Iron intake and bioavailability of iron from different meals - Elísabet Margeirsdóttir 1985- (2010)
Iron status among Icelandic infants and young children is considered worse than in the neighbouring countries. Iron status has never been assessed in Icelandic adolescents before. Iron requirements are high during periods of rapid growth and adolescent girls are considered one of the most vulnerable groups, because of menstruation and possible lack of bioavailable iron in the diet. Iron absorption depends highly on the composition of meals and therefore it is necessary to assess dietary iron for each meal and consider all factors that affect iron absorption, type of iron and iron fortification of foods. This is especially important when assessing iron requirements for populations. Information on the mean absorption from a diet has to be known but meal compositions vary greatly worldwide. The aims of this study were to evaluate the iron status among 9- and 15-year old Icelandic children and adolescents, assess their iron intake and estimate the amount of absorbed dietary iron in meals using a validated algorithm. Subjects were randomly selected with a cluster sampling from 18 different schools from four regions of Iceland. Of those 336 invited, 197 subjects participated both in the dietary survey and accepted to provide a blood sample and were selected for the present study (58% of the original sample). The diet was assessed using a repeated 24-hour recall. Serum ferritin (SF), haemoglobin (Hb) and mean corpuscular volume (MCV) was measured and used to detect iron deficiency and iron deficiency anemia. A validated algorithm by Hallberg and Hulthén was used to estimate absorbed iron from meals. All participants had Hb concentrations above the cut-off points and therefore none was diagnosed with iron deficiency anemia. Iron deficiency was observed in nine 15-year-old girls (SF ≤15 µg/L) corresponding to 18% of all the participating 15-year-old girls. The average iron intake reached the recommended daily reference value in all groups. Breakfast contributed most of the iron but had the least absorption. Calculated ...